Pengaruh Media Padi (Papan Diagram) Terhadap Hasil Belajar Matematika Kelas V SDN 029 Sumber Makmur Kecamatan Tapung Kabupaten Kampar Riau - Amalia, Via; Ain, Siti Quratul (CV. Rayyan Dwi Bharata, 2025)
This study aimed to examine the effect of PADI (Diagram Board) media on mathematics learning outcomes of fifth-grade students at SDN 029 Sumber Makmur, Tapung District, Kampar Regency, Riau. The research used a quantitative One Group Pretest-Posttest Design with 27 students selected through total sampling. Data analysis included validity test using Pearson, reliability using Cronbach’s Alpha, item difficulty, and discrimination indices. Normality (Shapiro-Wilk) and homogeneity tests showed normal data distribution and homogeneous variances. Validity test results showed r-count 0.406–0.812 r-table 0.381, reliability Cronbach’s Alpha 0.939, with average pretest 64,44 and posttest 85,37. Paired Sample t-Test revealed Sig. (2-tailed) = 0.000 0.05 and t-count = -5.750 t-table = 2.056, indicating a significant effect of PADI media on mathematics learning outcomes. PADI media is proven effective in improving students’ mathematics achievement.